Pengaruh Pembangunan Jalan dan Teknologi terhadap Produktivitas Ekonomi Masyarakat di Kecamatan Batahan Kabupaten Mandailing Natal - Zuhriatul Kumuliyah; Era Sonita; Rini Elvira; Amsah Hendra Doni (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This research is motivated by the level of economic productivity of MSMEs in Batahan District, Mandailing Natal Regency. Is there an increase or decrease in the economy with the construction of roads and the use of technology at this time. This research is a quantitative research with a descriptive approach. The type of data used in this study is primary data sources directly from the community through filling out questionnaires. The data analysis techniques used are validity tests, reliability, classical assumption tests, multiple linear regression tests and hypothesis tests. Based on the results of the analysis carried out using SPSS 26, the results obtained are (1) Based on the results of the hypothesis testing analysis, the T count value (0.188) <T table (1.882) and sig (0.0851)> 0.05. (2) Based on the results of the hypothesis testing analysis, the T count value (0.5897)> T table (1.882) and sig (0.000)<0.05. (3) Based on the results of the hypothesis testing analysis, the calculated F value (22.513) > F table (3.080) and sig (0.000) <0.05 (4) The results of the determination coefficient test show that the value obtained for the percentage of diversity in economic productivity variables that can be explained by road construction and technology variables is 29.6%, while the remaining 80.4% is explained by other factors that were not examined in this study.